To whom does Christianity belong? : critical issues in world Christianity - Daughrity, Dyron B., 1973- (Understanding world Christianity series., 2015)
To Whom Does Christianity Belong? is a question that is asked throughout the world today. In this exciting volume, an anchor to the Understanding World Christianity series, Dyron B. Daughrity helps readers map out the major changes that have taken place in recent years in the world's largest religion. By comparing trends, analyzing global Christian movements, and tracing the impact of Pentecostalism, interreligious dialogue, global missions, sexuality, birth rates, women, secularization, and migratory trends, Daughrity sketches a picture of a changing religion and gives the tools needed to understand it.